Biocontrol via mycoviruses: a neglected option for bioprotection? - van Diepeningen, Anne D. (Burleigh Dodds Series in Agricultural Science, 2021)
Virocontrol involves biocontrol of pathogens via hypovirulence-causing mycoviruses. This chapter discusses the characteristics of mycoviruses and the conditions that need to be met to make a successful virocontrol agent. The chapter describes one of the success stories so far, that of virocontrol of Cryphonectria parasitica, the chestnut blight pathogen. The chapter ends by reviewing future trends and where to find more information on mycoviruses and virocontrol.